Exploring the inherent mechanism of residents’ participation behavior in neighborhood regeneration projects: an empirical study using an extended IMB model in China - Fu, Xinyue; Zhuang, Taozhi; Huang, Ruopeng; Dong, Yaxian (Frontiers in Psychology, 2023)
Resident participation has gained increasing prominence and significance in the pursuit of sustainable neighborhoods regeneration. However, the current state of resident participation practices remains beset by several challenges, which present formidable impediments to the initiation and execution of neighborhood regeneration initiatives. To enhance the promotion of resident participation in neighborhood regeneration projects, there exists a compelling need to investigate its underlying mechanisms. Nevertheless, the existing body of research in this domain remains notably scarce. In light of this gap in the literature, the present study employs the extended Information-Motivation-Behavioral (IMB) model to examine the determinants and mechanisms influencing residents’ inclination and participation in neighborhood regeneration projects, with a specific focus on the Chinese context. Drawing upon data from 477 meticulously validated questionnaires administered to residents, the study applies structural equation modeling (SEM) to unravel the intrinsic dynamics of residents' participation behavior. The empirical findings of this research reveal that the availability of pertinent information, motivation cultivated through interactions with neighbors, and the involvement of external government entities all exert a significant impact on residents' willingness to participate. Notably, motivation emerges as the most influential factor. Furthermore, the study uncovers a direct influence of local government bodies on both residents' willingness and their actual participation, suggesting that government organizations can spearhead innovative strategies to bolster residents' willingness and furnish avenues for translating willingness into tangible participation. The outcomes of this study furnish an indispensable theoretical framework and offer policy recommendations that hold paramount importance for the deployment of novel interventions geared toward stimulating active involvement of residents in neighborhood regeneration.